2021
DOI: 10.3390/app11052044
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Successful Smart Campus Transitions: A Systems Thinking-SWOT Analysis Approach

Abstract: An identification of strengths, weakness, opportunities, and threats (SWOT) factors remains imperative for enabling a successful Smart Campus transition. The absence of a structured approach for analyzing the relationships between these SWOT factors and the influence thereof on Smart Campus transitions negate effective implementation. This study leverages a systems thinking approach to bridge this gap. Data were collected through a stakeholder workshop within a University of Technology case study and analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 74 publications
0
15
0
1
Order By: Relevance
“…Data mining supports harnessing analysis with deep learning architecture of neural networks for understanding campus end-user behaviour and requirements [3,17,134,135,[141][142][143]. Continuous improvement of smart campus infrastructure produces opportunities for research into smart campus applications, IT infrastructure, network, management, and applications [3,144,145]. Hence, a framework for improving the existing systems has used vertical and horizontal scalability, loss models, forecasting; statistics; and accuracy metrics.…”
Section: Implications On Continuous Improvement Of Smart Campus Infrastructurementioning
confidence: 99%
See 4 more Smart Citations
“…Data mining supports harnessing analysis with deep learning architecture of neural networks for understanding campus end-user behaviour and requirements [3,17,134,135,[141][142][143]. Continuous improvement of smart campus infrastructure produces opportunities for research into smart campus applications, IT infrastructure, network, management, and applications [3,144,145]. Hence, a framework for improving the existing systems has used vertical and horizontal scalability, loss models, forecasting; statistics; and accuracy metrics.…”
Section: Implications On Continuous Improvement Of Smart Campus Infrastructurementioning
confidence: 99%
“…Moreover, smart campuses are essential for meeting the United Nations' sustainable development goals (SDGs) like affordable and clean energy and sustainable cities and communities [1]. Likewise, campuses are smaller communities within cities that may serve as micro smart cities and an available framework for smart city development [3,4]. Awuzie et al [3] suggested that smart cities development in developing countries can be hinged on a clear strategic framework inclusive of governance, policymaking, and management of campuses.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations